Graduation Tree Planting (1907)
A photo of a graduating senior class planting their class tree in the Poly Grove. The first graduating class of 1907 planted an oak tree, so this is probably a later class. The student is using the shovel or "tree planting spade" that is pictured here: https://digital.lib.calpoly.edu/rekl-84713